2010
DOI: 10.1063/1.3380857
|View full text |Cite
|
Sign up to set email alerts
|

Thermonuclear ignition in inertial confinement fusion and comparison with magnetic confinement

Abstract: The physics of thermonuclear ignition in inertial confinement fusion (ICF) is presented in the familiar frame of a Lawson-type criterion. The product of the plasma pressure and confinement time Pτ for ICF is cast in terms of measurable parameters and its value is estimated for cryogenic implosions. An overall ignition parameter χ including pressure, confinement time, and temperature is derived to complement the product Pτ. A metric for performance assessment should include both χ and Pτ. The ignition parameter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
102
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 157 publications
(106 citation statements)
references
References 29 publications
2
102
0
2
Order By: Relevance
“…Several forms of a generalized Lawson criterion [9][10][11][12] have been developed to assess progress towards ignition. For ICF, hot spot formation and thermonuclear fuel assembly can be characterized by the neutron yield from primary deuterium-tritium reactions in the central hot plasma, D + T = 4 He(3.5 MeV) + n(14.1 MeV), and the ratio of down scattered to primary neutrons, N (10 − 12 MeV)/N (13 − 15 MeV), quantifying neutrons that have lost energy by scattering processes in the dense fuel plasma that surrounds the central hot plasma.…”
Section: Introductionmentioning
confidence: 99%
“…Several forms of a generalized Lawson criterion [9][10][11][12] have been developed to assess progress towards ignition. For ICF, hot spot formation and thermonuclear fuel assembly can be characterized by the neutron yield from primary deuterium-tritium reactions in the central hot plasma, D + T = 4 He(3.5 MeV) + n(14.1 MeV), and the ratio of down scattered to primary neutrons, N (10 − 12 MeV)/N (13 − 15 MeV), quantifying neutrons that have lost energy by scattering processes in the dense fuel plasma that surrounds the central hot plasma.…”
Section: Introductionmentioning
confidence: 99%
“…The ratio of alpha particle energy deposited in the hotspot to that generated by fusion ( ) is expected to decrease with perturbation amplitude. This is calculated using a kinetic model of alpha transport [4] in which computational macroparticles interact with the fluid via 'classical' drag and scatter rates [10,11]. The fluid is held stationary; this is necessary to associate a single value of with a single value of the perturbation amplitude.…”
Section: Effect Of Perturbations On Alpha Particle Confinementmentioning
confidence: 99%
“…A similar effect may occur in ICF, preventing the hotspot from maintaining a spherical core with a well-defined 3D radius. This would need to be accounted for in scaling studies such as [3] and [4].…”
Section: Introductionmentioning
confidence: 99%
“…From Newton's law, the hot-spot confinement time is related to the shell inertia like τ ∼ ffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffi ffi M=4πPR p . Combining these expressions shows that Pτ ∝ v × ρR [4]. This means that a successful ignition experiment must achieve high v and high ρR.…”
mentioning
confidence: 99%
“…The conditions necessary for ignition are related to a minimum requirement of the energy density delivered to the DT hot spot and the confinement time of that energy, or equivalently Pτ, the product of the hot-spot pressure (P), a measure of the hotspot energy density, and the energy confinement time (τ) [3]. Betti et al [4] showed that P is related to the implosion velocity (v) by balancing the hot-spot internal energy to the shell kinetic energy via 2πPR 3 ∼ θ 1 2 Mv 2 , where R is the radius of the hot spot, θ is the fraction of the shell kinetic energy converted to hot-spot energy, and M is the mass of the shell. Note that assuming a thin shell results in M ∼ 4πR 2 × ρR; where ρR is the areal density of the imploded shell.…”
mentioning
confidence: 99%